Evaluation of CD4 and CD8 in Patients Infected with Genital Wart Caused by Human Papilloma Virus in Babylon Province/Iraq - Nisreen Kaddim Radi (Journal of Global Pharma Technology, 2018)
Genital warts it’s a skin projection due to human papilloma virus infection (HPV) .Thirty skin lesion and sera were collected from patient (females) infected with genital warts that visit dermatological department of medical Moran city. Twenty sera was collected from healthy person used as control group.  The diagnosis of viral infectionwas achieved by dermatologist (specialist) and by using IgG anti HPV ELISA kit to detect papilloma virus in human serum, and ELISA testwas used to evaluate the level of CD4 and CD8 at patient with genital warts. The result demonstrates that:- 99% of samples dedicate positive for IgG anti HPV. Immunological study revealed that  :- decrease the ratio of CD4/CD8 at patient with genital wart( ratioCD4/CD8:-0.1), decrease in CD4 level at patient infected with genital warts compared with control group .CD8 increased at patient with genital warts compared with control group. There is significant differences between patient and control group, p value ≤ 0 .05.Keywords: HPV, Genital wart, CD4, CD8, Koliocyte.